(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Identifying the causative agent of tuberculosis, sending pathological materials to laboratories, conducting laboratory tests, ensuring food safety through biosynthesis and improving disease prevention measures.